Increasing Digital-Based Marketing in Nia Pekanbaru's Clothing Tailoring Micro Business - FIRMANSYAH; Irsyadi Zain (Universitas Darunnajah, Jakarta, Indonesia, 2023)
The development of information and communication technology is currently very rapid, almost every field of human life is dealing with information and communication technology, such as the social, political, cultural and economic fields; including in buying and selling transactions of society to be faster, easier and safer. People who want to buy their necessities of life only trade on digital or application-based. Based on the activities that have been carried out, namely training through digital marketing workshops for business actors, it can be concluded that this community service activity has been successfully carried out in a useful manner and in line with the goals of community service. This success is evidenced by the enthusiasm of business actors through an interesting question and answer process